Verse and Transmutation A Corpus of Middle English Alchemical Poetry (Critical Editions and Studies) - Timmermann, Anke (Brill, 2013)
Identifies and investigates a corpus of twenty-one anonymous Middle English recipes for the philosophers' stone dating from the fifteenth century.Verse and Transmutation: A Corpus of Middle English Alchemical Poetry identifies and investigates a corpus of twenty-one anonymous recipes for the philosophers' stone dating from the fifteenth century. These were circulated and received in association with each other until the mid-seventeenth century, when a number of them appeared in Elias Ashmole's Theatrum Chemicum Britannicum.These editions are the first to make this previously unidentified corpus available to researchers. The accompanying studies discover the complex histories of these alchemica, in plain and illuminated manuscripts, as anonyma and in attribution to famous authors, and in private and institutional, medical and academic book collections. Together, they offer novel insights into the role of alchemy and poetry in late medieval and early modern England.This title was made Open Access by libraries from around the world through Knowledge Unlatched.
Description based on print version record.
Knowledge Unlatched Pilot Collection
Keywords: Philosophy; Philosophy; Electronic books